ANALISIS SISTEM PEMBAYARAN QRIS TERHADAP PENINGKATAN UMKM DALAM TINJAUAN HUKUM EKONOMI SYARIAH DI PASAR TERONG - Reskyani, Nur; Bunyamin, Andi; Lawang, Hasanna; Akil, M; Alwi, Auliah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the Quick Response Code Indonesian Standard (QRIS) payment system to improve Micro, Small, and Medium Enterprises (MSMEs) at Terong Market, Makassar, and to analyze its compliance with the principles of Islamic Economic Law. This study uses a qualitative research method with a case study approach. Data were obtained through observation, interviews, and documentation. Research informants consisted of one management staff member of Terong Market, twelve MSME traders, and five consumers who use QRIS. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing and verification. The results show that the implementation of QRIS provides various benefits for MSMEs, including simplifying the transaction process, accelerating payments, increasing transaction security, and helping with more orderly financial recording. The existence of QRIS can also increase consumer convenience, thus contributing to increased transaction activity and turnover for some traders. However, the implementation of QRIS still faces several obstacles, such as low digital literacy among some traders, the process of disbursement of funds (settlement) that is not received directly, and the existence of service fees (Merchant Discount Rate/MDR) which is still considered to reduce business profits. Furthermore, increased revenue is not only influenced by QRIS usage but also by business location, type of merchandise, and consumer demand. From the perspective of Sharia Economic Law, the use of QRIS is essentially permissible because it functions solely as a means of payment and does not contain elements of usury, gharar, or maysir. Service fees (MDR) can be categorized as ujrah (payment) for payment system services as long as they are conducted transparently and agreed upon by all parties. Thus, QRIS can be an instrument that supports the digitalization of MSMEs while remaining in line with the principles of Sharia Economic Law.